Autologous lymphapheresis for the production of chimeric antigen receptor T cells. Issue 5 (24th February 2017) - Allen, Elizabeth S.; Stroncek, David F.; Ren, Jiaqiang; Eder, Anne F.; West, Kamille A.; Fry, Terry J.; Lee, Daniel W.; Mackall, Crystal L.; Conry‐Cantilena, Cathy
Abstract : BACKGROUND: The first step in manufacturing chimeric antigen receptor (CAR) T cells is to collect autologous CD3+ lymphocytes by apheresis. Patients, however, often have leukopenia or have other disease‐related complications. We evaluated the feasibility of collecting adequate numbers of CD3+ cells, risk factors for inadequate collections, and the rate of adverse events. STUDY DESIGN AND METHODS: Apheresis lymphocyte collections from patients participating in three CAR T‐cell clinical trials were reviewed. Collections were performed on the COBE Spectra by experienced nurses, with the goal of obtaining a minimum of 0.6 × 10 9 and a target of 2 × 10 9 CD3+ cells. Preapheresis peripheral blood counts, apheresis parameters, and product cell counts were analyzed. RESULTS: Of the 71 collections, 69 (97%) achieved the minimum and 55 (77%) achieved the target. Before apheresis, the 16 patients with yields below the target had significantly lower proportions and absolute numbers of circulating lymphocytes and CD3+ lymphocytes and higher proportions of circulating blasts and NK cells than those who achieved the target (470 × 10 6 lymphocytes/L vs. 1340 × 10 6 lymphocytes/L, p = 0.008; 349 × 10 6 CD3+ cells/L vs. 914 × 10 6 CD3+ cells/L, p = 0.001; 17.6% blasts vs. 4.55% blasts, p = 0.029). Enrichment of blasts in the product compared to the peripheral blood occurred in four patients, including the two patients whose collections did not yield the minimum number of CD3+ cells. Apheresis complications occurred in 11 patients (15%) and, with one exception, were easily managed in the apheresis clinic. CONCLUSIONS: In most patients undergoing CAR T‐cell therapy, leukapheresis is well tolerated, and adequate numbers of CD3+ lymphocytes are collected.